Excitation and coherent control of spin qudit modes in silicon carbide at room temperature - Soltamov, V. A.; Kasper, C.; Poshakinskiy, A. V.; Anisimov, A. N.; Mokhov, E. N.; Sperlich, A.; Tarasenko, S. A.; Baranov, P. G.; Astakhov, G. V.; Dyakonov, V. (Nature communications, 2019)
One of the challenges in the field of quantum sensing and information processing is to selectively address and coherently manipulate highly homogeneous qubits subject to external perturbations. Here, we present room-temperature coherent control of high-dimensional quantum bits, the so-called qudits, associated with vacancy-related spins in silicon carbide enriched with nuclear spin-free isotopes. In addition to the excitation of a spectrally narrow qudit mode at the pump frequency, several other modes are excited in the electron spin resonance spectra whose relative positions depend on the external magnetic field. We develop a theory of multipole spin dynamics and demonstrate selective quantum control of homogeneous spin packets with sub-MHz spectral resolution. Furthermore, we perform two-frequency Ramsey interferometry to demonstrate absolute dc magnetometry, which is immune to thermal noise and strain inhomogeneity. High-dimensional quantum bits advance the application of quantum sensing and information processing technologies but suffer from the low spectral selectivity and working temperature. Here the authors present the selective excitation and control of spin qudits modes based on an ensemble of silicon vacancy defects in silicon carbide at room temperature.